You've been warned : a novel - Patterson, James, 1947- (Little, Brown and Co., 2007)
Believing that everything she has ever wanted is within her grasp, New York City photographer Kristin Burns suffers a recurring nightmare of increasing violence that spills over into her waking life and convinces her that everyone she loves is in mortal danger.